RATIONAL FOR THE USE OF COCONUT OIL-BASED ANTI-MYCOTIC PESSARIES TO COMBAT RECURRENT VAGINAL INFECTION: IN VITRO/IN VIVO EVALUATION AND PRELIMINARY PROSPECTIVE CLINICAL INVESTIGATION - Kamel, Rabab; Abbas, Haidy (International Journal of Applied Pharmaceutics, 2018)
Objective: Coconut oil (CO) was used in combination with metronidazole in order to prepare vaginal pessaries ameliorating the use, delivery and efficacy of the anti-mycotic treatment. Methods: To prepare the metronidazoleâ€“loaded pessaries, different lipids, namely: suppocire NA15 (SNA), suppocire NAIS10 (SIS), suppocire AM (SAM) and ovucire WL 2944 (OWL) were used alone or in combination with coconut oil in a ratio of 1:1. Prepared pessaries were subjected to characterization and evaluation of physical properties, drug release, anti-microbial effect, in vivo studies and histopathological examination. Results: In the case of all the lipids, coconut oil improved the physical properties which can allow better use and performance of the pessaries. Among the prepared pessaries, the OWL/CO-based pessary (P8) showed the highest drug release profile (P<0.05). Characterization was done using X-Ray diffraction. Microbiological study showed the superiority of OWL/CO-based pessaries over OWL-based pessaries at different time intervals. Histopathological studies of the vagina of female Wistar rats showed that in the case of the Candida albicans-infected group treated with the selected pessary, the mucosal and muscular layer returned to its normal structure, in addition to the disappearance of the cauliflower-like projections and the newly formed blood capillaries, seen in the Candida albicans-infected group. The questionnaire done in volunteers suffering from recurrent vaginal infection reported a significant decrease (reaching 93 %) in the severity of the symptoms, after the use of the suggested pessaries (P8) (P<0.05). Also, the suggested product had high patient acceptability. The results reported after the use of P8 were better than those of AmrizoleÂ® vaginal suppository. Conclusion: The current study can present a successful, effective and easy to use product with low cost and minimal side effects.